Deception: from ancient empires to Internet dating - Harrington, Brooke (Stanford Univ. Press, 2009)
Introduction : beyond true and false / Brooke Harrington -- Dealing with deception in biology / Carl T. Bergstrom -- Paltering / Frederick Schauer and Richard Zeckhauser -- Thoughts, feelings, and deception / Mark G. Frank -- Why most people parse palters, fibs, lies, whoppers, and other deceptions poorly / Maureen O'Sullivan -- Digital doctoring : can we trust photographs? / Hany Farid -- Digital deception : the practice of lying in the digital age / Jeffrey T. Hancock -- Cognitive hacking : detecting deception on the web / Paul Thompson -- Leaps and lapses of faith : exploring the relationship between trust and deception / Guido Möllering -- Tying the truth in knots : trustworthiness and accountability in the Inka khipu / Gary Urton -- Does rumor lie? : narrators, trust, and the framing of unsecured information / Gary Alan Fine -- Crocodile tears, or, Method acting in everyday life / Tom Lutz -- Deception and trust in health crises / Ford Rowan -- Responding to deception : the case of fraud in financial markets / Brooke Harrington -- Military deception in the information age : scale matters / William Glenney IV -- The pleasures of lying / Kenneth Fields